The Flying Dutchman - Wagner, Richard (Italy : Pagoda books Simon and Schuster, 1987)
This is an opera. The pages that follow provide a superb visual rendering of this highly dramatic tale.
Keywords: Wagner, Richard, -- 1813-1883.; Theatre; Opera; Richard Wagner; Flying Dutchman; Opera; Wagner, Richard, -- 1813-1883.